Environmental Security through Soil & Water Conservation and Watershed Management for the Hilly and high rainfall regions of Peninsula India - P., Samraj.; B., Raghunath (Journal of Soil and Water Conservation, 2022)
Conservation and proper use of soil and water on agricultural and non-agricultural lands is a key to nation’s economy and the wealth of the plains depends mainly upon the health of the hills. The hilly and high rainfall areas of Peninsular India comprise of Western and Eastern ghats andto a little extent Vindhyas and Satpuras covering the States of Kerala, Tamil Nadu, Karnataka, Andhra Pradesh, Orissa, Goa and Maharashtra. They form the catchment areas of important river systems which are harnessedfir hydropower, irrigation, drinking water supply, recreational purposes, etc. Mismanagement and over exploitation of natural resources in this region have created problems of degradation in the environment. Steep slopes with high amounts of rainfal rainfall occurring with high intensities during the monsoon periods cause severe soil erosion followed by siltation in reservoirs, land slides, flash floods, etc. , especially when the top vegetal cover of the natural eco- system • • tampered with for raising seasonal crops, faulty cultivation, mining, etc The Central Soil and Water Conservation Research & Training Institute, Research Centre, Udhagamandalam and other allied Institutions representing this tract have a number of useful research findings which are highlighted in this paper, besides presenting the description of this tract, problems encountered, solutions identified for the same through a multi-disciplinary research programme on Soil and Water Conservation and Waterhsed Management The need for total resources conservation through Soil and Water Conservation and Watershed Management for these hills to ensure proper utilisation of land and water resources for achieving environmental security is stressed